Real-Time detection and tracking moving vehicles for video surveillance systems using FPGA - Abdulraheem Fadhel, Mohammed; Al-Shamaa, Omran; Husain Taher, Bahaa (International Journal of Engineering and Technology, 2018)
With the growth of the electronic and communication devices, computer vision has become an significant application of smart cities. A smart city is controlled by smart autonomous systems. Many algorithms have been developed to satisfy these smart cities. This paper concerned with addressing the moving objects (vehicles) by using morphological techniques. For computational cheapness. The simulation has been built by a MATLAB 2012a and its implementation was done using Xilinx-ISE 14.6 (2013) XC3S700A-FPGA board that provides an exceptional tool for mixing between two platforms, the ISE 14.6(2013) and the MATLAB (2012a) platforms. MATLAB provides components for FPGA that invoke Verilog code of Xilinx platform, to avoid the size weakness of XC3S700A-FPGA board.Â